Evaluation of hotel quality attribute importance through fuzzy correlation coefficient - Ban, Olimpia-Iuliana; Tara, Ioan Gheorghe; Bogdan, Victoria; Tuşe, Delia; Bologa, Simona Gabriela (Technological and Economic Development of Economy, 2016)
An indirect method of calculation of the importance of attributes as the fuzzy correlation between the performance of attributes and the overall satisfaction was proposed in a recent paper. We apply the method to the results of a survey with respect to the quality of hotel services in Oradea (Romania). Different representations of the answers as triangular fuzzy numbers, as well as distinct analyzes to compare the hierarchies of the attributes with respect to the experience with the hotel and the motivation of the travel are considered. First published online: 30 Mar 2016